The 'rejuvenating factor' TIMP‐2 is detectable in human blood components for transfusion. Issue 5 (26th October 2020) - Hoefer, Julia; Dal‐Pont, Christian; Jochberger, Stefan; Fantin, Raffaella; Schennach, Harald
Abstract : Background and Objectives: Tissue inhibitor of metalloproteinases 2 (TIMP‐2) is a protein suspected to be crucial in numerous physiological and pathological processes such as morphogenesis, tissue remodelling and metastasis suppression. In animal models, the administration of TIMP‐2 to aged mice improved their cognitive functions. Therefore, one can hypothesize that differences in TIMP‐2 levels between blood donors and recipients might influence cognitive functions also in humans. However, the stability of TIMP‐2 during processing and storage of blood components for transfusion has not been intensively investigated so far. This study determined TIMP‐2 concentrations in fresh‐frozen plasma (FFP), erythrocyte concentrate (EC) and pathogen‐inactivated platelet concentrate (PI‐PC) depending on the donor's demographic factors age and gender. Materials and Methods: Tissue inhibitor of metalloproteinases 2 was measured in FFP ( n = 30), EC ( n = 12) and PI‐PC ( n = 12) using a Q‐Plex single‐plex immunoassay for chemiluminescence‐based detection. Absolute quantification of TIMP‐2 was performed with Q‐view software. Fresh umbilical cord plasma was used as a positive control. Results: Tissue inhibitor of metalloproteinases 2 was detected in FFP (30/30 samples), EC (11/12 samples) and PI‐PC (12/12 samples). The median TIMP‐2 concentration in EC (17·2 ng/ml; range: 0–26·5 ng/ml) was significantly lower compared with FFP (63·4 ng/ml; range: 44·4–87·3 ng/ml) or PI‐PC (69·9 ng/ml; range: 39·9–83·6 ng/ml). Across all blood components, TIMP‐2 levels are comparable in male and female donors and independent of age. Conclusion: Tissue inhibitor of metalloproteinases 2 is detectable and stable in FFP, PI‐PC and, in low concentration, EC. It can be hypothesized that TIMP‐2 will be transmitted to recipients during transfusion.